أسباب فقد الأسنان في المنطقة الساحلية - لايقة, عمار (Latakia University Journal -Medical Sciences Series, 2019)
تتأثر الحالة الفيزيولوجية للفم و الوجه و الفكين بشكل كبير بفقدان الأسنان، و من هنا كان الهدف من هذه الدراسة الإحصائية تحري أهم الأسباب المؤهبة لقلع الأسنان في المنطقة الساحلية في سوريا و علاقتها مع العمر و الجنس. تم لهذا الغرض دراسة استمارات تشخيصية ل 1433 مراجعاً بهدف قلع أسنانهم، و قد قسمت أسباب القلع إلى النخور، أمراض أنسجة داعمة، أهداف تعويضية، أسباب أخرى. لقد كان النخر السني أو أحد مضاعفاته هو السبب الرئيس لقلع الأسنان (51.84%)، يليه بالدرجة الثانية أمراض الأنسجة الداعمة بنسبة (41.81%). فقد النساء أسنانهنّ بسبب النخر بنسبة (54.96%) أكثر من الذكور (49.18%). نستخلص من نتائج هذا البحث أن نخر الأسنان و أمراض الأنسجة الداعمة هما المشكلتان الرئيستان المسببتان لفقدان الأسنان في الساحل السوري، و أن نخر الأسنان هو السبب الأهم لفقدان الأسنان، كما أن هناك علاقة وثيقة ما بين سبب فقدان الأسنان و العمر. The physiological status of the mouth, maxilla, and face is affected by tooth loss. The main objective of this statistical study is to examine the most important factors that trigger tooth extraction on the Syrian coast. A total of 1433 dental patients (males and females) aged between 18 and 74 years are diagnosed for tooth extraction. Caries or one of their complications (51.84%) are the main cause leading to extraction; then, periodontal cases (41.81%) come second. Females lose most of their teeth at a higher rate (54.96%) than males (49.18%) via caries. This study provides evidence that caries and periodontal diseases are the substantial problems of tooth loss on the Syrian coast, and that caries remain a major cause of tooth loss due to the higher prevalence of this condition. Moreover, there is a close correlation between age and the reason for tooth loss.